The Educational Challenges of Muslim Youths in A Muslim Community - Shamhuna, Abdul Aziz (Ijtimā iyya Journal of Muslim Society Research, 2024)
The education of Muslim youths in a Muslim community is facing significant challenges that hinder the academic and socio-economic progress of the youths despite the government's efforts to improve access to education. Muslim youths in various Muslim communities continue to experience low enrolment, high dropout rates, and poor academic performance. Lack of access to quality education is a major issue for Muslim youths which is serving as the basis for this article. The article used a mixed-methods approach and qualitative data collection methods to gather information from key stakeholders, including Muslim youths, parents, teachers, community leaders, and education experts. Findings from the research revealed that Muslim youths are capable of acquiring knowledge to the extent of becoming teachers and obtaining higher positions in society. Nevertheless, the community has done very little to ensure the effective participation of their children and Muslim youths in the acquisition of knowledge. Analysis revealed that the current situation of education is susceptible to breakdown, due to a plethora of challenges, and many inhabitants have renounced education as fruitless. Community-based interventions, Policymakers formulating policies and programs that prioritize education for marginalized groups, and innovative educational models, such as e-learning and mobile learning can help to improve access to quality education for Muslim youths. These recommendations can be used to curb the situation and put it on track, as well as create awareness of the need for the acquisition of secular education, especially among Muslim youths